A meta-analysis on the price elasticity and income elasticity of residential electricity demand. (10th November 2018) - Zhu, Xing; Li, Lanlan; Zhou, Kaile; Zhang, Xiaoling; Yang, Shanlin
Abstract: Price elasticity and income elasticity can quantitatively measure the impact of price volatility and income diversity on household electricity demand. To analyze household electricity demand and better identify the main factors affecting residential electricity demand elasticity in previous literature, a meta-analysis based on a comprehensive and systematic summary of 103 articles is presented in this study. The influencing factors are identified, with a weighed least squares (WLS) linear regression model to evaluate their strength. The price elasticities and income elasticities are discussed from three dimensions, namely short-term, long-term and unmarked. The results show that residential electricity demand is almost price-inelastic and income-inelastic in the short-term. But in the long-term, some residential electricity demand is price-elastic and income-elastic. The results also reveal that residential electricity demand elasticity is affected by many factors, such as time interval and sample period. These conclusions can support the formulation of more effective electricity price and energy policy. Graphical abstract: Image 1 Highlights: A meta-analysis based on the estimates of residential electricity demand elasticity. Determinants for price elasticity and income elasticity are investigated. Residential electricity demand is almost inelastic in the short-term. Elasticity variation can largely be explained by multiple factors.